Relationship between Patient’s Satisfaction and level of emotional Intelligence in Nurses Working in Tertiary Care Hospital: Relationship between Patient’s Satisfaction and level of emotional Intelligence - Masih, Orung Zaib; Mukhtar, Madiha; Masih, Sarfraz (Pakistan Journal of Health Sciences, 2023)
Emotional intelligence is the ability to sense what is going on, to understand how it feels while in that circumstance, to effectively analyses and consider other people’s thoughts and feelings, and to respond accordingly. It can be defined as the ability to correctly recognize one’s own and others’ emotions. Objectives: To determine the association between patients’ satisfaction and level of emotional intelligence (EI) in nurses working in medical and surgical department in tertiary care hospitals, Lahore. Methods: A correlational study design was used to carry on this study. This study was conducted at Mayo Hospital and Social Security Hospital Kot Lakh Pat Lahore. The duration of the study was six months from Jan, 2023 to June; 2023.The study participants were registered nurses (both male and female) and admit patients (both male and female) there. Purposive sampling technique was used n=265 participants were recruited. To assess the performance among nurses and patients, an observational checklist was used. Data of the study participants was entered in statistical software SPSS version 21.0 and was analyzed accordingly. Results: This study shows that there are statistically non-significant differences between patient’s satisfaction and emotional intelligence. The results revealed a non-significant association between nurses’ emotional intelligence and patient’s satisfaction, as p-value is p=.381 which is non-significant. So, we reject the alternative hypothesis and accept the null hypothesis. Conclusions: It is concluded that nurse’s emotional intelligence has no relationship on patient’s satisfaction, Nurse’s emotional intelligence and its association with patient’s satisfaction, which results were non-significant.